Влияние формы поперечного сечения магнитопровода электромагнита постоянного тока на его быстродействие - Байда, Е.И. (Електротехніка і електромеханіка, 2011)
The paper considers a DC electromagnet speed computation problem as function of the magnetic conductor sectional shape. Qualitative and quantitative characteristics are given.